A functional copy number variation in the WWOX gene is associated with lung cancer risk in Chinese - Yang, Lei; Liu, Bin; Huang, Binfang; Deng, Jieqiong; Li, Hongbin; Yu, Bolan; Qiu, Fuman; Cheng, Mei; Wang, Hui; Yang, Rongrong; Yang, Xiaorong; Zhou, Yifeng; et al. (Human molecular genetics, 2013)
WW domain-containing oxidoreductase (WWOX) is a tumor suppressor that has been reported to lose function due to genetic alterations in several cancers. WWOX maps to the common chromosomal fragile site FRA16D and several copy number variations (CNVs) were found within this gene. In this study, we investigated the association between the CNVs of WWOX and lung cancer risk in four independent case-control studies, which are on 2942 lung cancer cases and 3074 cancer-free controls of southern, eastern and northern Chinese. A common CNV-67048 was genotyped by the Taqman real-time PCR, and its biological effect was accessed with protein expression and sequencing assays. We found that in comparison with the common 2-copy genotype, the carriers of loss variant genotypes (1-copy or 0-copy) had a significantly increased risk of lung cancer (adjusted OR = 1.39, 95% CI = 1.24-1.55, P = 9.01×10(-9)) in a dose-response manner (Ptrend = 1.12 × 10(-10)), and the WWOX protein expressions in lung cancer tissues were significantly lower (P = 0.036), accompanying a higher rate of exons absence (P = 0.021) in subjects with loss genotypes of CNV-67048. Our data suggest that the loss genotypes of CNV-67048 in WWOX predispose their carriers to lung cancer; this might be related with altered WWOX gene expression and exons absence in them.